Utilization of Moringa oleifera leaf meal as a protein source in diets for Cirrhinus mrigala: effects on growth, body composition, and hematology - Faisal, Muhammad; Hussain, Syed Makhdoom; Sarker, Pallab K.; Ali, Shafaqat; Al-Ghanim, Khalid A.; Yousaf, Zeeshan (Frontiers in Sustainable Food Systems, 2024)
Introduction In the current study, Cirrhinus mrigala was used as an animal model to investigate the impacts of Moringa oleifera leaf meal (MOLM) on their overall performance reared in six earthen ponds. Methods In this study, fishmeal (FM) was substituted with MOLM at various levels in the diet: 0% (control), 10, 15, 20, 25, and 30%, for a six-month feeding trial. A total of 270 fish with 15 fingerlings (15.31 ± 0.12 g/fish) stocked in each of the six earthen ponds in triplicates. Results When compared to other experimental and control groups, analyses revealed that fish given a diet having 10% MOLM had the highest growth performance (final weight: 422.32 g, weight gain: 406.97 g). Fingerlings fed a diet which substituted with 10% of FM with MOLM showed the greatest results for body composition (crude protein: 19.31%; crude fat: 3.01%). The results of hematology, i.e., WBCs: 7.65 × 103 mm−3, PLT: 58.38, hemoglobin level: 8.52 g 100 mL−1, PCV: 25.12%, MCHC: 30.45%, MCH: 48.81 pg., MCV: 159.50 fl, also showed that 10% MOLM was the optimum level for FM substitution. Furthermore, the outcomes of body mineralization (P, Ca, Na, Mn, Fe, Mg, Zn, K, and Cu, 1.06, 0.92%, 5.53 mg/g, 9.90 ug/g, 54.62 ug/g, 3.09%, 3.81 ug/g, 8.31%, and 3.76 ug/g respectively) also indicated that 10% level was the best. Conclusion Conclusively, the current study found that substituting 10% of FM with MOLM in the diet of C. mrigala fingerlings improved growth performance, carcass, hematology, and mineral status.